Depression and anxiety symptoms associated with internet addiction and non-suicidal self-injury in Chinese adolescent students - a network analysis - Mohan Ma; Chuman Xiao; Wenwen Ou; Xiaoshu Li; Yumeng Yang; Yafei Chen; Chunxi Ke; Jin Liu; Bangshan Liu; Yunjing Li; Siqi Yang; Yimei Lu; et al. (BMC Psychiatry)
Abstract Background Non-suicidal self-injury (NSSI) and Internet addiction (IA) are adolescent maladaptive behaviors that are receiving increasing attention and exerting a significant impact on both adolescent development and public health, and depressive and anxiety symptoms are two of the most associated risk factors of NSSI and IA. This study aimed to use network analysis to explore the associations between NSSI, IA, and depression-anxiety symptoms. Methods A total of 1799 adolescents aged 12–16 completed self-report questionnaires. We conducted a conditional independence test on NSSI and IA controlling for depression and anxiety, and constructed a partial correlation network and a direct acyclic graph incorporating NSSI, IA, nine depressive symptoms (from PHQ-9), and seven anxiety symptoms (from GAD-7). Results Results suggested that there was no significant correlation between NSSI and IA after controlling for depression (P = 0.25) and anxiety (P = 0.14) symptoms. IA was mainly associated with Anxiety symptoms, and NSSI was associated with both anxiety and depressive symptoms. Suicidal ideation and afraid were causally related to NSSI, and restlessness was causally related to IA. Conclusions This study suggests that NSSI and IA are conditionally independent of depression and anxiety. Specific symptoms including suicidal ideation, afraid, and restlessness are the key intervention targets of NSSI and IA behaviors.